CASE STUDY: ORAL HYPOGLYCEMIC DRUGS OVERDOSE INDUCED GENERALISED TONICCLONIC SEIZURES - KUCHIPUDI, ANVESH KUMAR; PORANKI, VATHSALYA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Metformin is an oral hypoglycemic agent of the biguanide class, and glimepiride is an oral hypoglycemic agent of the sulfonylurea class frequently used to treat Type-II diabetes mellitus. Under certain conditions, overdose or long-term use of metformin and glimepiride can cause lactic acidosis and hypoglycemia. Metformin overdose can cause severe hypoglycemia in the absence of other anti-diabetic drugs. Potential mechanisms of metformin-induced hypoglycemia include decreased hepatic glucose production, decreased glucose absorption, and low oral intake. Hypoglycemia, in turn, leads to loss of consciousness, headache, confusion, and neurological symptoms such as insomnia, delirium, and in rare conditions may lead to coma, seizures, and death. Here, this case study is of 23-years-old female patient and non-diabetic presented with alleged consumption of metformin (8 g), glimepiride (32 mg) with three-episodes of generalized tonic-clonic seizures (GTCS), fever with chills, and loss of consciousness. In general, diabetic patient’s hypoglycemia condition can be more often due to drug overdosage or dietary restrictions. However, in non-diabetic patients, hypoglycemia is considered a jeopardy situation because it may lead to several fatal effects.